Contribution á l’étude des propriétés électroniques et magnétiques des DMS et DMO pour la spintronique. - RAMI Redouane (Faculté des Sciences de Rabat, 2021)
For innovating spintronic applications, it is a key issue to find ferromagnetic semiconductors at room temperature. The aim of this thesis is to study the electronic structure and magnetic properties of DMS and DMO.
Contribution to the study of electronic and magnetic properties of DMS and DMO for Spintronics.
Keywords: Propriétés Magnétiques; Structure Électronique; Méthode KKR; CPA; Spintronique; DMS/DMO; Ferromagnétisme; semi; métallique.; Physique